Selection effect of heritability and association in sugarcane (Saccharum officinarum) of important traits - SHARMA, M L; SINGH, PRATAP (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during 1995-96 on 60 genotypes in selected and unselected population of sugarcane (Saccharum officinarum L.) of different origins, viz Coimbatore (,Co ’), Coimbatore-Shahjahanpur (’CoS ’) and Bihar-Orissa (’BO’). The mean value in selected population was higher showing 22.81 to 31.80% increase in stalk weight and 8.64 to 22.96% in number of internode. The lowest mean 1.37-6.46% was increased for hand refractometer compared with the unselected population. The range of select fOil differential was 6.25% compared with unselected population. The high coefficient of variation and moderate heritability were found for stalk weight, height, girth and number and length of internode whereas the low coefficient of variation and high heritability were found for hand refractometer brix in both the population. The low magnitude of variation and high heritability were exhibited in selected population. A negative genotypic correlation was found between brix and stalk weight and girth. The brix Â was positively and significantly correlated with number and length of internodes and stalk height in both the populations. It was noticed in. selected population that the genetic magnitude increased in positive direction and decreased in negative direction for most of the characters in each category which is considered in sugarcane improvement.